Instrumen Literasi Digital Guru Menggunakan Model Rasch - Weni Lestari; Indah Wigati; Moh Ismail Sholeh; Desi Pramita (Chemistry Education Department of Education and Teaching Faculty, 2022)
The development of digital technology provides a significant role in the learning process. However, its utilization is very closely related to the skills possessed by the teacher. These skills can be identified with digital literacy instruments. This study aims to measure the accuracy and feasibility of digital literacy instruments for teachers. The type of research used is descriptive quantitative with a non-experimental/survey research design. The research sample consisted of 96 teachers teaching at the State Aliyah Madrasah in Palembang City, South Sumatra. The research data was obtained from an analysis of the teacher's digital literacy instrument questionnaire. Data were analyzed using the Rasch model. The results showed that the item separation value was 3.54 where the instrument could identify the respondent's group. The item reliability value is 0.93 which is categorized as very good. The Cronbach Alpha value is 0.90 which indicates that the value is very good and consistent. The raw variance explained by measures is 31.8% where the instrument is actually able to measure what it should measure. The classification of the difficulty level of the instrument categorized as very difficult, difficult, easy, and very easy. The results of the DIF analysis show that there are no items that are biased or only biased and detrimental to one gender. So it can be concluded that the instrument meets the requirements and can be used as material to measure the digital literacy abilities of teachers at MAN Palembang City.